2010
DOI: 10.1159/000316576
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy: An Increasing Problem for the Elderly

Abstract: As populations become older all over the world, allergic reactions in elderly persons will be encountered more often in the future. Up to now, there has been much more literature on allergy prevalence in childhood than on allergy diseases in adults. As a challenge to epidemiology, allergic disorders in elderly persons may be masked by various symptoms corresponding with a general age-induced decline of physiological functions, including vitamin D deficiency and gastric pH increase. How much structural and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
1
12
0
1
Order By: Relevance
“…It remains unclear what risk factors exist for the development of food allergy in adult life. It has been suggested that age-related changes might alter the potential for the onset of food allergy in older adults, for example, vitamin D deficiency in adulthood and medications to inhibit gastric acidity may both increase the likelihood of late-onset food allergy [41]. Few prevalence studies have assessed the age of onset of reported food allergy in adults although Vierk et al [37] found that 54% of reported reactions in adults commenced aged 20 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear what risk factors exist for the development of food allergy in adult life. It has been suggested that age-related changes might alter the potential for the onset of food allergy in older adults, for example, vitamin D deficiency in adulthood and medications to inhibit gastric acidity may both increase the likelihood of late-onset food allergy [41]. Few prevalence studies have assessed the age of onset of reported food allergy in adults although Vierk et al [37] found that 54% of reported reactions in adults commenced aged 20 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…Structural and functional changes or effects caused by drugs (e.g. acid-suppression medications), in addition to immunological alterations encountered at old age, might be responsible for food allergy development in the elderly [5]. Elderly people are at higher risk of food allergy due to their aging immune systems.…”
Section: Gutmentioning
confidence: 99%
“…Frequently late-onset food allergy occurs after exercise and consuming food to which the patients are allergic. Food allergy may present with a variety of symptoms involving cutaneous (e.g., urticaria, angioedema, eczema), respiratory (rhinitis, asthma), gastrointestinal (diarrhea), or generalized anaphylactic reactions [5]. …”
Section: Gutmentioning
confidence: 99%
See 1 more Smart Citation
“…5-8%. Ezen allergiák nagy részét az érintettek a felnôtté válás folyamán kinövik, tolerancia alakul ki, így a felnôttkori prevalencia csupán 1-3% (2,3,(6)(7)(8). Gyermekekben leggyakrabban a tej, tojás, dió, mogyoró, hal és a szója okoz allergiát.…”
Section: Kulcsszavak: éLelmiszer Allergia -éLelmiszer Intoleranciaurtunclassified